Alternative building blocks sources for poly (ethylene terephthalate): A short review with socio-economical points of view - Sandei, Benjamin; Massardier, Valérie; Brunel, Raphael (Frontiers in Materials, 2022)
The objectives of circularity are often focused on recycling, but combining use of alternative building blocks such as bio-sourced ones for virgin materials with ability for recycling seems to be a relevant challenge. Unfortunately, the volumes of rather new bio-based plastics, such as Poly (lactide) (PLA), seem be too low to allow the development of new recycling chains in the next years. Therefore, these bio-plastics are not likely to be recycled at large scale, reducing their interest when considering their whole life cycle. Nevertheless, continuing to produce petroleum-based plastics and searching for a way to recycle them seems not to be a self-sufficient solution. Indeed, in order to reconciliate recycling and bio-based plastics, a strategy is to focus on the production of conventional plastics, such as poly (ethylene terephthalate) (PET), from renewable resources while ensuring their recycling in existing chains. In this context, this review focuses on alternative building blocks sources to produce PET, for which recycling seems relevant and developed. Although still produced in small quantities, some alternative sources for building block production have been able to establish themselves in the industrial landscape. Nevertheless, there is still little industrialization and the synthons are often produced in small quantities. Most of the discoveries are still confined to laboratory studies with some pilot tests for part of them. It should be emphasized that, even if some synthons are already commercialized, research is active with the aim of improving yields, discovering cleaner catalysts, reducing energy consumption. The review describes alternative routes and sources for the production of PET, not only with technological but also socio-economical points of view with discussion on their potentials and limits. The different routes proposed display promising advantages to be improved by research studies. Nevertheless, producing bio-sourced polymers at a large-scale could lead to problems of access to resources. A more local economy involving smaller volumes of material and adapting to the resources of the territory could be an alternative. The review could help in orientating research contributing to a circular economy depending less on non renewable resources, considerationg technological and socio-economical points of view.